(untitled) (Estudios de Historia de España, 2021)
This study analyses the evolution in the life cycle of families living in a city of Extremadura in the modern times, the city of Trujillo. In a strictly methodological level, it has been used the method of reconstruction families. The article examines the organization of family structures that developed in this city at the end of the Old Regime, in a period of political transition in which the documentary sources of the twenties of nineteenth century have allowed us to observe a family structure clearly defined in Extremadura and it can be extrapolated to the entire peninsular.